Investigation of exergetic and exergo-sustainability metrics for high by-pass turbofan engine at different power settings - Aygun, Hakan (Wiley, 2021)
This paper investigates influences of several throttle settings on several exergetic and exergo-sustainability parameters by employing thermodynamic principles for high by-pass turbofan engine as named PW4000 engine. First, energy efficiency of the PW4000 is found to vary between 9.77% and 37.69% due to rising from 5544 RPM to 9169 RPM. Considering exergetic results on component basis, rising power setting leads to increase exergy efficiency of the components. Also, the combustor of PW4000 belongs to lowest exergy efficiency throughout 19 RPMs. Namely, exergy efficiency of the combustor increases from 69.14% to 86.31% whereas that of LPT raises from 92.01% to 93.25% owing to the increase in RPM. Considering sustainability parameters for whole engine, exergy efficiency of PW4000 varies from 9.13% to 35.26% whereas its exergetic sustainability index increases from 0.276 to 1.238 throughout RPM values. Furthermore, environmental effect factor of PW4000 decreases from 3.26 to 0.807 due to rising RPM value. According to these results, it is revealed that there are generally nonlinear relationship between thermodynamic parameters and power settings. To measure exergetic metrics of turbofan engines for different running points can allow researchers to find optimum RPM value of the engine in terms of thermodynamic sustainability.
Keywords: efficiency; exergy; gas turbines; power setting; sustainability